Motivasi Belajar Mahasiswa: Peran Dukungan Sosial Melalui Mediator Religiositas - Raden Rachmy Diana; Adam Anshori; Sumedi P. Nugraha; Yoga Achmad Ramadhan; Lukman Lukman (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2021)
Students’ motivation to learn has many important influences on university students. Motivation can increase learning involvement, learning autonomy, social presence and enrolment, critical thinking skills, writing skills, problem-solving skills, and learning achievement. This study aims to determine the effect of social support on student learning motivation through the mediator of religiosity. The research subjects were 202 students (male and female) at an Islamic university. The measuring instruments used are the Islamic Religiosity Scale from Nashori, the Multidimensional Scale of Perceived Social Support from Zimet, Dahlem, Zimet, and Farley, and the Learning Motivation Scale from Utami, Nashori, and Rachmawati. The data were analyzed using stepwise regression. The results showed that social support and religiosity influenced learning motivation. So, social support influenced learning motivation with religiosity as a full mediator.